ENGLISH TABOO WORDS IN SEX EDUCATION TV SERIES - Cindy Eliza Ramadhani Lubis; Syahron Lubis; Dian Marisha Putri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The purposes of this research are to determine the types of taboo words, the functions of taboo words, and in what context taboo words are uttered by the characters in the TV series. This study employed descriptive qualitative method. The sources of the data were 8 videos from the first season of Sex Education TV series and their transcripts. In analyzing the data, the theory of Wardhaugh (2014) was used to describe types and functions of taboo words and the theory of Fromkin (2005) to describe in what context taboo words are uttered in the TV series. The results of this research show that there are data of taboo words which are categorized into seven types; they are sex term, death, excretion, bodily function, religious matter, mother-in-law, and the left hand. The findings suggest that the characters use taboo words mostly to draw attention and to show contempt.